Atherosclerotic cardiovascular disease risk and small dense low-density lipoprotein cholesterol in men, women, African Americans and non-African Americans: The pooling project. (February 2023) - Schaefer, Ernst J.; Ikezaki, Hiroaki; Diffenderfer, Margaret R.; Lim, Elise; Liu, Ching-Ti; Hoogeveen, Ron C.; Guan, Weihua; Tsai, Michael Y.; Ballantyne, Christie M.
Abstract: Background and aims: Elevated small dense low-density lipoprotein-cholesterol (sdLDL-C) has been reported to be associated with increased atherosclerotic cardiovascular disease (ASCVD) risk. Our aims were to determine whether direct and calculated sdLDL-C were significant independent ASCVD risk factors in sex and race subgroups. Methods: In a total of 15, 933 participants free of ASCVD at baseline (median age 62 years, 56.7% female, 19.7% African American) fasting plasma lipids and sdLDL-C were measured by standardized automated methods. All subjects were followed for 10 years for incident ASCVD, which developed in 9.7% of subjects. SdLDL-C values were also calculated. Univariate and multivariate analyses were carried out to assess for independent associations with incident ASCVD after adjustment for all standard risk factors. Results: All standard risk factors were significantly associated with incident ASCVD on univariate analysis, as were direct and calculated sdLDL-C. These latter parameters were also significant when added to the pooled cohort risk equation. However, associations were significantly stronger for direct sdLDL-C and were not significant for calculated values once direct values were in the model. In contrast to calculated values, top quartile direct sdLDL-C was significantly independently associated with incident ASCVD versus bottom quartile values in all subjects and subgroups, except African Americans (hazard ratios ≥1.50, p  < 0.01). Subjects with direct values ≥ 50 mg/dL versus <25 mg/dL had significantly higher independent ASCVD risk in all groups (hazard ratios >1.49, all p  < 0.01). Conclusions: Having a direct small dense low-density lipoprotein cholesterol value ≥ 50 mg/dL is a significant independent ASCVD risk-enhancer. Graphical abstract: Image 1 HIGHLIGHTS: An elevated direct sdLDL-C value > 50 mg/dL is an independent atherosclerotic cardiovascular disease (ASCVD) risk factor. An elevated calculated sdLDL-C is not an independent ASCVD risk factor. An elevated direct sdLDL-C value > 50 mg/dL is an ASCVD risk-enhancer.